Potential of Banana Peel and Coconut Fiber as Biosorbents for Pb Heavy Metals in Water - Amala, Wega Nasyita; Winarsih, Winarsih (LenteraBio : Berkala Ilmiah Biologi, 2024)
Excessive amounts of the heavy metal Pb in the environment can cause pollution due to its high toxicity, so it needs to be treated using an efficient and economical adsorption method using banana peel (Musa paradisiaca L.) and young coconut fiber (Cocos nucifera). This research aims to identify the potential of kepok banana peel, young coconut fiber, and a combination of the two as biosorbents for heavy metal lead. This research used a Completely Randomized Design (CRD) with 2 treatment factors, namely the type of biosorbent (kepok banana peel; young coconut fiber; a combination of both) and the mass of the biosorbent (0.5; 1; 2 grams). This research was repeated 3 times, resulting in a total of 27 experimental units. The parameters measured were levels of the heavy metal lead before and after treatment. Data were analyzed using statistical methods using 2-way ANOVA, then continued with the Duncan test. The research results showed that the optimum mass for reducing Pb levels was a mass of 1 grams with an absorption percentage of 99.01±0.381%. Optimum adsorption effectiveness was found in the combined biosorbent type with an absorption percentage of 99.85±0.214%.